Direct quantitation of psychosine from alkaline-treated lipid extracts with a semi-synthetic internal standard - Xuntian Jiang; Kui Yang; Xianlin Han (Journal of Lipid Research, 2009)
Psychosine is an important bioactive sphingolipid metabolite and plays an essential role in the pathogenesis of Krabbe's disease. Herein, we extended shotgun lipidomics for the characterization and quantitation of psychosine in alkaline-treated crude lipid extracts by using neutral loss scan of 180 amu (i.e., galactose) in the positive-ion mode. Specifically, we semi-synthesized N,N-dimethyl psychosine and used it as an internal standard for quantitation of psychosine. After characterization of the fragmentation patterns of psychosine and the selected internal standard and optimization of the experimental conditions, we demonstrated that a broad linear dynamic range for the quantitation of psychosine and a limit of detection at a concentration of low fmol/μl were achieved using this approach. The developed method is generally simpler and more efficient than other previously reported methods. Multiple factors influencing quantitation of psychosine were extensively examined and/or discussed. The levels of psychosine in diabetic mouse nerve tissue samples were determined by the developed methodology. Collectively, the developed approach, as a new addition to the shotgun lipidomics technology, will be extremely useful for understanding the pathways/networks of sphingolipid metabolism and for exploring the important roles of psychosine in a variety of physiological and pathological conditions.